Propuesta de un modelo de sistema de control interno en la empresa ABC S.A.S. (2021)
The object of study of this work corresponds to the elaboration of a proposal where the guidelines required for the design of a solid internal control system that is aligned with the needs of the company are evidenced. The foregoing in order to monitor and control the different operations and thus ensure that the organization has support when it comes to achieving institutional objectives, for this it was necessary to evaluate the internal control system currently implemented by the company, carry out a diagnosis and finally propose a proposal for an internal control model based on the Committee of Sponsoring Organizations of the Treadway Commission (COSO)